Terapia de relaxamento com imagem guiada sobre a ansiedade e a dor em pacientes submetidos à cirurgia bariátrica: ensaio clínico randomizado - FELIX, Márcia Marques dos Santos (2018)
Relief of human pain is considered an important mission of health professionals. However, despite advances in scientific knowledge and improvements in pain management strategies, their diagnosis and treatment are questionable, yet far from adequate and effective. Postoperative pain is a combination of tissue injury, pain and anxiety. Inadequate pain relief in the perioperative setting has negative effects on surgery outcomes and patient satisfaction. Effective management of pain after bariatric surgery results in early mobilization and reduces postoperative complications. Given the complexity of perioperative anxiety and the process of postoperative pain caused by the stress of surgery, relieving these symptoms requires a creative and varied approach. Guided imagery relaxation therapy is a widely used intervention that can be effective in promoting clinical outcomes, including surgery. The present study aimed to evaluate the effect of relaxation therapy with guided imagery on state-anxiety and cortisol in the immediate preoperative period and on pain, cytokines and cortisol in the immediate postoperative period in patients submitted to video-laparoscopic bariatric surgery. This is an experimental, randomized, parallel, triple-blind clinical trial conducted according to the recommendations of the Consolidated Standards of Reporting Trials (CONSORT), performed at the outpatient clinic of Digestive System Surgery and in the Clinical Surgery Unit of a teaching hospital in the interior of the State of Minas Gerais. Twenty-four patients undergoing video-laparoscopic bariatric surgery were randomly divided into two groups: the experimental group, in which the patients received relaxation therapy with guided image and control group, in which the patients received standard care (bed rest). Data collection was performed on the patient's bed, once a day, in each of the two times analyzed in this study, namely: T1 - immediate preoperative period (up to 24 hours before surgery) and T2 - immediate postoperative period (up to 24 hours after surgery), by means of an instrument elaborated specifically for this study. Descriptive analyzes were used for quantitative variables, t-test for analysis of differences between anxiety scores, Mann-Whitney non-parametric test for cytokine analysis, Wilcoxon non-parametric test for intra-group pain intensity scores, nonparametric test of Mann-Whitney for analysis of the means of the difference between the pain intensity scores between the groups and, finally, the Pearson correlation coefficient, to check the correlation between the trait-anxiety and pain intensity. The research was approved by the Research Ethics Committee of the institution and was registered in the Brazilian Registry of Clinical Trials platform. The Chi-Square test showed that the groups were homogeneous and comparable, whereas the ShapiroWilk test proved that there was normality between them. The results showed that guided imagery relaxation therapy reduced state anxiety scores (p = 0.005) and cortisol levels in the immediate preoperative period (p <0.001). In the immediate postoperative period, as a complementary therapy to the adopted analgesia, the intervention provided a better control of postoperative pain (p <0.001), associated with a decrease in the response to surgical stress, evidenced by the decrease in cortisol levels in the experimental group, with statistically significant difference (p = 0.010). There was an increase in IL-10 and a reduction in the cytokines IL-6, IL-8 and TNF-α released in response to surgical stress, however, without statistical significance. It was concluded that guided imagery relaxation therapy was effective in reducing anxiety-state and cortisol levels in the immediate preoperative period, minimizing pain intensity and reducing cortisol levels in the immediate postoperative period, in patients submitted to video-laparoscopic bariatric surgery.